The community of ten after the Athens summit - Rudolf Hrbek (Intereconomics, 1984)
Twenty-five years after its foundation, the European Community is in a blind alley. Not one of the urgent problems facing it was brought closer to solution at the summit conference held in Athens at the end of last year. Professor Rudolf Hrbek takes stock.
Keywords: 330; EC